Handbook of advanced industrial and hazardous wastes treatment - Wang, Lawrence K.; Hung, Yung-Tse; Shammas, Nazih K. (Advances in industrial and hazardous wastes treatment series., 2010)
Most industrial and hazardous waste management resources cover the major industries and provide conventional in-plant pollution control strategies. Until now however, no book or series of books has provided coverage that includes the latest developments in innovative and alternative environmental technology, design criteria, managerial decision methodologies, and regional and global environmental conservation. The new "Handbook of Advanced Industrial and Hazardous Wastes Treatment"--Together with its predecessor, the "Handbook of Industrial and Hazardous Wastes Treatment"--forms a complete and up-to-date resource that contains all the necessary technical information on hazardous industrial waste treatment. Providing in-depth coverage of treatment and management technologies in wide-ranging industries that readers simply won't find anywhere else, this cutting-edge text addresses wastes in areas including metal finishing, food processing, milk production, foundries, and chemical manufacturing